2009
DOI: 10.1002/art.24838
|View full text |Cite
|
Sign up to set email alerts
|

Erythrocyte sedimentation rate, C‐reactive protein level, and serum amyloid A protein for patient selection and monitoring of anti–tumor necrosis factor treatment in ankylosing spondylitis

Abstract: Objective. To study the usefulness of erythrocyte sedimentation rate (ESR), C-reactive protein (CRP), and serum amyloid A (SAA) for response prediction and monitoring of anti-tumor necrosis factor (anti-TNF) treatment in ankylosing spondylitis (AS) patients. Methods. Patients were included consecutively before starting etanercept or infliximab treatment. ASsessment in Ankylosing Spondylitis (ASAS) response, defined as a 50% improvement or an absolute improvement of 2 points of the Bath Ankylosing Spondylitis D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
68
2
16

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(93 citation statements)
references
References 16 publications
7
68
2
16
Order By: Relevance
“…Acutephase reactants may also have a predictive value for treatment response. One study on patients with ankylosing spondylitis treated with anti-TNF showed that higher baseline levels of ESR and CRP may be associated with a better response rate, while Burmester et al demonstrated the opposite (21)(22). We confirmed that higher baseline DAS28, as well as high acute phase reactants in terms of C3 and CRP, might be associated with a poorer response to anti-TNF.…”
Section: Complement Disease Activity and Anti-tnf Treatmentsupporting
confidence: 75%
“…Acutephase reactants may also have a predictive value for treatment response. One study on patients with ankylosing spondylitis treated with anti-TNF showed that higher baseline levels of ESR and CRP may be associated with a better response rate, while Burmester et al demonstrated the opposite (21)(22). We confirmed that higher baseline DAS28, as well as high acute phase reactants in terms of C3 and CRP, might be associated with a poorer response to anti-TNF.…”
Section: Complement Disease Activity and Anti-tnf Treatmentsupporting
confidence: 75%
“…15 A combination of elevated basal levels of CRP and SAA show a greater predictive value for clinical response (81%) in patients with AS treated with anti-TNF. 41 Our study documented elevated serum concentration levels of MMP-3 in patients with SpA compared to healthy individuals. An important data set has evaluated serum MMP-3 as a biomarker that refl ects disease activity because it is expressed in a variety of cells within the joint, such as macrophages, fibroblasts, and chondrocytes, and in response to various stimuli and pro-infl ammatory cytokines, such as TNF-α.…”
Section: Discussionsupporting
confidence: 52%
“…Previously acute phase reactants such as ESR and CRP had weakly to moderately but significant relations with the disease activity in AS. 4,[6][7][8] On the other hand, NLR has been proposed to be a marker to evaluate systemic inflammatory condition in various chronic inflammatory diseases. [10][11][12][13][14][15][16][17] However, the relationship between disease activity in AS and NLR has not been fully demonstrated yet.…”
Section: Discussionmentioning
confidence: 99%
“…2 Beside subjective scales such as Mander and Maastricht Ankylosing Spondylitis Enthesitis Indices, 3 a lot of objective laboratory markers like erythrocyte sedimentation rate (ESR), C-reactive protein (CRP), immunoglobulin A, G and M, complements C3 and C4, interferon-gamma, interleukin-4, alpha-1-antitrypsin, and serum amyloid A were suggested to be used in evaluating disease activity in AS. [4][5][6][7][8] The pathogenesis of AS is controversial but recent studies have revealed the roles of both neutrophils and lymphocytes. 1,9 Leukocyte count and its subtypes are also well-known inflammatory markers in several diseases.…”
mentioning
confidence: 99%